2015
DOI: 10.1039/c4np00167b
|View full text |Cite
|
Sign up to set email alerts
|

The marine actinomycete genus Salinispora: a model organism for secondary metabolite discovery

Abstract: This review covers the initial discovery of the marine actinomycete genus Salinispora through its development as a model for natural product research. A focus is placed on the novel chemical structures reported with reference to their biological activities and the synthetic and biosynthetic studies they have inspired. The time line of discoveries progresses from more traditional bioassay-guided approaches through the application of genome mining and genetic engineering techniques that target the products of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
137
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 137 publications
1
137
0
2
Order By: Relevance
“…A successful example is the relatively novel genus Salinispora , of which several species have been isolated from marine sediments of Guam, Palau and the Red Sea producing salinosporamides, inhibitors of the 20S proteasome (Jensen et al ., 2015). A promising underexplored habitat is also the human body: Recently, it has been shown that the nasal colonizing organism Staphylococcus lugduensis produces a novel peptide antibiotic (Peschel pers commun; Nature in press).…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…A successful example is the relatively novel genus Salinispora , of which several species have been isolated from marine sediments of Guam, Palau and the Red Sea producing salinosporamides, inhibitors of the 20S proteasome (Jensen et al ., 2015). A promising underexplored habitat is also the human body: Recently, it has been shown that the nasal colonizing organism Staphylococcus lugduensis produces a novel peptide antibiotic (Peschel pers commun; Nature in press).…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…Tandem mass spectrometry (MS/MS)-based analyses visualized as molecular networks (57) led to the identification of known metabolites, including rifamycins, saliniketals, and staurosporine, in the extracts of both CNY-679 and CNS-820 Table S3). All of these compounds have been previously reported from S. arenicola (49), and all three metabolite groups contained strain-specific analogs. Out of 119 bacterial metabolites, 55 were present in the extracts of both S. arenicola strains, while 24 were unique to S. arenicola CNS-679, and 40 were unique to S. arenicola CNS-820.…”
Section: Resultsmentioning
confidence: 99%
“…It is comprised of three named species, Salinispora arenicola, Salinispora tropica, and Salinispora pacifica (46,47), which are well delineated despite sharing 99% 16S rRNA gene sequence identity (48). Notably, these bacteria are a rich source of secondary metabolites (49), which have proven to be key phenotypic (50) and genotypic (45) features that differentiate the species. Secondary metabolism also distinguishes the competitive strategies employed by S. arenicola and S. tropica; in particular, the production of rifamycin antibiotics by S. arenicola contributes to its broad inhibitory capacity compared to that of the faster-growing S. tropica (18).…”
mentioning
confidence: 99%
“…18 Since freshwater systems harbor distinct environmental selection pressures and growth conditions, it was suspected that globally endemic freshwater microbial populations existed. This postulate was argued until the advent of molecular-based screening techniques.…”
Section: Resultsmentioning
confidence: 99%